An Analysis of Ten Grade Students’ Speaking Ability in Expressing Intentions at SMA Pembangunan UNP - Meisya Aulia Fikra; Carbiriena Solusia (Journal of English Language Teaching, 2022)
This research was conducted to determine whether the students' an appropriate vocabulary and comprehensing of the words were appropriate or not in expressing intentions. This type of research is descriptive qualitative. The population in this study were first-grade students of MIPA 3 SMA Pembangunan UNP, totaling 1 class. Then, 20 students were selected as the sample for this study using saturated sampling. Making short dialogues then appropriate vocabulary and comprehension word tests to measure their ability to express intentions using the research categories instrument. After data collection, the text will be assessed by 2 raters. The results of data analysis showed that the Cronbach Alpha value of .359 was the result of the correlation in this study showing the value of r = 0.444. The findings of this study, in general, show between students' vocabulary mastery and comprehensive words in learning expressing intentions. According to research, students have difficulty in using an appropriate vocabulary but are good at a comprehension of words.